Porous carbon-based composite gel material and preparation method thereof

By combining cellulose with porous carbon and adding two-dimensional nanomaterials, a high-performance porous carbon-based composite gel was prepared, which solved the problems of insufficient performance and limited application of porous carbon materials, and achieved the improvement of the mechanical properties and application of the materials. Expand, suitable for a variety of high-performance materials fields.

CN119306998APending Publication Date: 2025-01-14DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411434840.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing porous carbon materials have problems inadequate performance and are difficult to expand production and recycling in applications, especially in terms of mechanical properties and electrical conductivity. Their applications are limited by solid state and are difficult to expand into the field of flexible electronic devices.

Method used

By combining cellulose with porous carbon, porous carbon-based composite gel is prepared by ionic liquid dissolution, ultrasonic dispersion and two-dimensional nanomaterial enhancement, the high specific surface area, electrical conductivity and mechanical properties of the material are improved, and the material is condensed by The glue form expands its application.

Benefits of technology

The prepared porous carbon-based composite gel material exhibits excellent mechanical properties, conductivity and flexibility, is suitable for energy storage, adsorption materials and catalytic materials, and can be used in flexible electronic devices and filtered gel membranes, expanding porous carbon and improves the possibility of recycling and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306998A_ABST
    Figure CN119306998A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a porous carbon-based composite gel material with excellent performance, which comprises the following steps: (1) adding cellulose with a mass fraction of 1-10 wt% into an ionic liquid, and stirring at a temperature of T1 to obtain a cellulose ionic liquid solution with a certain concentration; (2) pretreating porous carbon, reducing the temperature of the cellulose ionic liquid to T2, adding the pretreated porous carbon into a cellulose ionic liquid solution according to a certain mass ratio at a constant temperature, stirring and ultrasonically dispersing to obtain an ionic liquid mixed solution of porous carbon and cellulose; (3) adding a small amount of the two-dimensional nano-material as an inorganic reinforcing agent into the ionic liquid mixed solution of the porous carbon and the cellulose, stirring and mixing, and carrying out ultrasonic dispersion at a certain power; and (4) defoaming the obtained final mixed solution, regenerating and washing with a coagulating bath to obtain the porous carbon-based composite hydrogel, and drying to obtain the porous carbon-based composite aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a porous carbon-based composite gel, belongs to the field of material science, and can be applied to the fields of environmental functional materials, catalysis, energy storage, seawater desalination, etc. Background Art

[0002] Porous carbon materials have the advantages of high specific surface area, adjustable pore size, high conductivity, stable chemical properties and low cost. These excellent properties make them widely used in aerospace, medicine, electrochemistry and petrochemical fields. They can be used for adsorption, catalysis, separation, insulation, purification and energy storage, etc., and have high value. Therefore, it is of great significance to develop zero-pollution, low-energy consumption and scalable production of high-performance porous carbon-based composite materials.

[0003] Cellulose is a natural, abundant, renewable, green polymer. Due to its unique asymmetric chemical structure, cellulose has excellent mechanical strength and flexibility. If cellulose is composited with porous carbon, the porous carbon can be embedded in the cellulose, and the interaction can greatly improve the overall material performance, which is conducive to higher utilization and better hydrophilicity. At the same time, a composite gel material with a certain specific surface area, strong mechanical properties, and excellent hydrophilicity is obtained, which is more conducive to recycling and reuse. Summary of the invention

[0004] The purpose of the present invention is to provide a porous carbon-based composite gel material with excellent performance and a new preparation method thereof.

[0005] The object of the present invention is to provide a method for preparing a porous carbon-based composite gel material with excellent performance, comprising the following steps:

[0006] S1: adding cellulose with a mass fraction of 1 wt% to 10 wt% into the ionic liquid, stirring at a temperature of T1 to obtain a cellulose ionic liquid solution of a certain concentration;

[0007] S2: pretreating the porous carbon, lowering the temperature of the cellulose ionic liquid to T2, adding the pretreated porous carbon to the cellulose ionic liquid solution at a certain mass ratio at a constant temperature, stirring and ultrasonically dispersing, to obtain a porous carbon and cellulose ionic liquid mixed solution;

[0008] S3: adding a small amount of two-dimensional nanomaterials as inorganic reinforcing agents into the ionic liquid mixture of porous carbon and cellulose, stirring and mixing, and ultrasonically dispersing at a certain power;

[0009] S4: degassing the final mixed solution, regenerating it with a coagulation bath, washing it to obtain a porous carbon-based composite hydrogel, and then drying it to obtain a porous carbon-based composite aerogel.

[0010] In the preparation method of the present invention, the cellulose raw material includes one or more of microcrystalline cellulose, plant straw, dissolving pulp, cotton linters, etc.

[0011] In the preparation method of the present invention, the solvent is an imidazolium salt ionic liquid, a pyridinium salt ionic liquid, a novel choline and non-imidazole salt ionic liquid, etc.

[0012] In the preparation method of the present invention, in step S1, the temperature T1 is in the range of 60 to 120° C., and the processing time is 2 to 12 hours.

[0013] The preparation method described in the present invention, wherein the porous carbon described in step S2 includes biochar, petroleum-based porous carbon, carbon molecular sieve, activated carbon fiber and modified or doped porous carbon, etc.; the pretreatment method includes ball milling, mortar grinding, etc.; the mass ratio of porous carbon to cellulose is 0.1wt% to 98wt%.

[0014] In the preparation method of the present invention, the temperature T2 in step S2 is in the range of 50 to 100°C.

[0015] The method described in the present invention, wherein in step S3, the two-dimensional nanomaterial is graphene, MXene, molybdenum disulfide, etc.; the mass fraction of the two-dimensional nanomaterial relative to cellulose is 0 to 15wt%.

[0016] The method of the present invention, wherein in step S4, the coagulation liquid is water, ethanol, 5wt% Na2SO4, 5wt% H2SO4, 5wt% H2SO4 / 5wt% Na2SO4, 3% HAc and 5wt% (NH)2SO4; the drying step is freeze drying, supercritical CO2 drying, natural drying or oven drying.

[0017] The second aspect of the present invention provides a high-performance porous carbon-based composite gel material, which is prepared according to the above-mentioned preparation method.

[0018] The third aspect of the present invention provides a method for preparing a high-performance porous carbon-based composite gel material, comprising the following steps:

[0019] S1: adding cellulose with a mass fraction of 1 wt% to 10 wt% into the ionic liquid, stirring at a temperature of T1 to obtain a cellulose ionic liquid solution of a certain concentration;

[0020] S2: pretreating the porous carbon, lowering the temperature of the cellulose ionic liquid to T2, adding the pretreated porous carbon to the cellulose ionic liquid solution at a certain mass ratio at a constant temperature, stirring and ultrasonically dispersing, to obtain a porous carbon and cellulose ionic liquid mixed solution;

[0021] S3: adding a small amount of two-dimensional nanomaterials as inorganic reinforcing agents into the ionic liquid mixture of porous carbon and cellulose, stirring and mixing, and ultrasonically dispersing at a certain power;

[0022] S4: degassing the final mixed solution, regenerating it with a coagulation bath, washing it to obtain a porous carbon-based composite hydrogel, and then drying it to obtain a porous carbon-based composite aerogel.

[0023] The inventors have prepared a porous carbon-based composite gel material for the first time through research. The composite gel prepared by this method has high specific surface area, electrical conductivity, flexibility and mechanical properties, and has excellent performance as energy storage material, adsorption material, carrier material, etc.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a porous carbon-based composite gel material and a preparation method thereof, and proposes a new idea of ​​directly constructing a composite gel using porous carbon; compared with traditional porous carbon, it has better mechanical properties and a mixed porous structure, which is conducive to recycling and reuse; it can be directly used as a self-supporting electrode, expanding the application of porous carbon to the field of flexible electronic devices, etc.; it can be directly used as a filtering gel membrane; compared with cellulose gel, it has better conductivity and catalytic properties, and has excellent performance as an environmental functional material, electrode material or catalytic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The porous carbon-based composite gel material prepared in Example 1.

[0026] Figure 2 The porous carbon-based composite gel material prepared in Example 2.

[0027] Figure 3 This is the SEM image of the porous carbon-based composite gel material prepared in Example 1. DETAILED DESCRIPTION

[0028] In order to better understand the contents of the present invention, the present invention is further described below in conjunction with examples and drawings. However, the implementation methods of the present invention are not limited thereto, and the scope of protection claimed by the present invention is not limited to the scope represented by the examples. For process parameters not specifically noted, conventional techniques can be referred to.

[0029] Example 1

[0030] First, weigh 40 g of 1-butyl-3-methylimidazolium chloride [BMIM] Cl into a 250 mL three-necked flask, and add 3.478 g of microcrystalline cellulose into the three-necked flask, pass nitrogen for 30 minutes, and then heat the oil bath temperature T1 to 95°C (at about 75°C, with rotor magnetic stirring), for about 2-3 hours, the ionic liquid is completely dissolved to form a light yellow transparent liquid, and 8 wt% cellulose ionic liquid is obtained.

[0031] Secondly, the porous carbon was pretreated by ball milling (500 rpm, ball milling for 3 min), and after the temperature of the cellulose ionic liquid was reduced to T2, the pretreated porous carbon was added to the cellulose ionic liquid solution at a certain mass ratio at a constant temperature, the mass ratio of the porous carbon to the cellulose was 0.1 wt%, and stirred and ultrasonically dispersed to obtain a porous carbon and cellulose ionic liquid mixture;

[0032] Finally, 0.67 g of reduced graphene oxide ionic liquid solution and 2.78 g of biochar were added to the cellulose ionic liquid solution of the dissolving pulp, and the mixture was magnetically stirred at 95 ° C for 30 min. The resulting mixture was transferred to a 100 mL beaker and degassed by ultrasonic treatment (100 W, 60 ° C) for 40 min. After that, the mixture was immersed in deionized water for regeneration to obtain a regenerated composite gel.

[0033] Example 2-3

[0034] The regenerated composite gel was prepared according to the method of Example 1, except that the oil bath temperature T1 was modified to 60°C and 120°C, which are Examples 2-3 respectively.

[0035] Embodiment 4-6

[0036] Regenerated composite gels were prepared according to the method of Example 1, namely Examples 4-6, except that the microcrystalline cellulose was changed to plant straw, dissolving pulp, and cotton linters.

[0037] Example 7

[0038] The regenerated composite gel was prepared according to the method of Example 1 except that the mass ratio of porous carbon to cellulose was 98 wt %.

[0039] Example 8

[0040] The regenerated composite gel was prepared according to the method of Example 1, except that the graphene used as the two-dimensional nanomaterial was changed to MXene and molybdenum disulfide, and the mass fraction of the two-dimensional nanomaterial relative to cellulose was 15 wt %.

[0041] Example 9

[0042] First, cellulose was added to the ionic liquid (the mass ratio of dissolving pulp to 1-butyl-3-methylimidazolium chloride was 5:95), mixed and heated to 95° C. and stirred for 4 hours under a nitrogen atmosphere until the cellulose was completely dissolved in the ionic liquid to obtain a cellulose ionic liquid.

[0043] Secondly, after the temperature of the cellulose ionic liquid was lowered to 70°C, nitrogen-doped corncob porous carbon and graphene (the mass ratio of porous carbon, cellulose and graphene was 90:9:1) were added at a constant temperature, stirred for 10 minutes and then ultrasonicated for 30 minutes to obtain a porous carbon and cellulose ionic liquid mixture;

[0044] Finally, the final mixed solution was transferred to a beaker for degassing, and then the mixture was immersed in ethanol for regeneration to obtain a columnar porous carbon-based composite hydrogel, which was repeatedly washed with deionized water until 0.1 mol mL -1 The AgNO3 solution was added to the immersion solution until no precipitation was detected. The columnar porous carbon-based composite aerogel was obtained by freeze drying.

[0045] The present invention provides a porous carbon-based composite gel material and a preparation method thereof, and proposes a new idea of ​​directly constructing a composite gel using porous carbon; compared with traditional porous carbon, it has better mechanical properties and a mixed porous structure, which is conducive to recycling and reuse; it can be directly used as a self-supporting electrode, expanding the application of porous carbon to the field of flexible electronic devices, etc.; it can be directly used as a filtering gel membrane; compared with cellulose gel, it has better conductivity and catalytic performance, and has excellent performance as an environmental functional material, electrode material or catalytic material.

[0046] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon-based composite gel material, characterized in that: The following steps are involved: S1: adding cellulose with a mass fraction of 1 wt% to 10 wt% into the ionic liquid, stirring at a temperature of T1 to obtain a cellulose ionic liquid solution of a certain concentration; S2: pretreating the porous carbon, lowering the temperature of the cellulose ionic liquid solution to T2, adding the pretreated porous carbon to the cellulose ionic liquid solution at a certain mass ratio at a constant temperature, stirring and ultrasonically dispersing, to obtain a porous carbon and cellulose ionic liquid mixed solution; S3: adding a small amount of two-dimensional nanomaterials as inorganic reinforcing agents into the ionic liquid mixture of porous carbon and cellulose, stirring and mixing, and ultrasonically dispersing at a certain power; S4: degassing the final mixed solution, regenerating it with a coagulation bath, washing it to obtain a porous carbon-based composite hydrogel, and then drying it to obtain a porous carbon-based composite aerogel.

2. The method for preparing a porous carbon-based composite gel material according to claim 1, characterized in that: The cellulose includes one or more of microcrystalline cellulose, plant straw, dissolving pulp, and cotton linters.

3. The method for preparing a porous carbon-based composite gel material according to claim 1, characterized in that: The solvent is an imidazolium salt ionic liquid, a pyridinium salt ionic liquid, a novel choline ionic liquid and a non-imidazole salt ionic liquid.

4. The method according to claim 1, characterized in that: In step S1, the temperature T1 is in the range of 60 to 120°C, and the processing time is 2 to 12 hours.

5. The method according to claim 1, characterized in that The porous carbon in step S2 includes biochar, petroleum-based porous carbon, carbon molecular sieve, activated carbon fiber and modified or doped porous carbon, etc.; the pretreatment method includes ball milling, mortar grinding, etc.; the mass ratio of porous carbon to cellulose is 0.1wt% to 98wt%.

6. The method according to claim 1, characterized in that The temperature T2 in step S2 is in the range of 50 to 100°C.

7. The method according to claim 1, characterized in that In step S3, the two-dimensional nanomaterial is graphene, MXene, molybdenum disulfide, etc.; the mass fraction of the two-dimensional nanomaterial relative to the cellulose is 0 to 15 wt%.

8. The preparation method according to claim 1, characterized in that: In step S4, the coagulation liquid is water, ethanol, 5wt% Na2SO4, 5wt% H2SO4, 5wt% H2SO4 / 5wt% Na2SO4, 3% HAc and 5wt% (NH)2SO4; the drying step is freeze drying, supercritical CO2 drying, natural drying or oven drying.

9. A high-performance porous carbon-based composite gel, characterized in that: It is prepared according to the method according to any one of claims 1 to 8.

10. A method for preparing a porous carbon-based composite gel material, characterized in that: The following steps are involved: S1: adding cellulose with a mass fraction of 1 wt% to 10 wt% into the ionic liquid, stirring at a temperature of T1 to obtain a cellulose ionic liquid solution of a certain concentration; S2: pretreating the porous carbon, lowering the temperature of the cellulose ionic liquid to T2, adding the pretreated porous carbon to the cellulose ionic liquid solution at a certain mass ratio at a constant temperature, stirring and ultrasonically dispersing, to obtain a porous carbon and cellulose ionic liquid mixed solution; S3: adding a small amount of two-dimensional nanomaterials as inorganic reinforcing agents into the ionic liquid mixture of porous carbon and cellulose, stirring and mixing, and ultrasonically dispersing at a certain power; S4: degassing the final mixed solution, regenerating it with a coagulation bath, washing it to obtain a porous carbon-based composite hydrogel, and then drying it to obtain a porous carbon-based composite aerogel.

11. A high-performance porous carbon-based composite gel, characterized in that: Prepared according to the method of claim 10.